# Answer on Algebra Question for Francis

Question #659

kq/(x+a)^2-kq/(x-a)^2

Expert's answer

kq/(x+a)^2 - kq/(x-a)^2 =

= (kq * (x-a)^2)/((x+a)^2 * (x-a)^2) - (kq * (x+a)^2)/((x-a)^2 * (x+a)^2) =

= (kq * (x^2-2*x*a+a^2))/((x+a)^2 * (x-a)^2) - (kq * (x^2+2*x*a+a^2))/((x-a)^2 * (x+a)^2) =

= (kq * (x^2-2*x*a+a^2))/((x^2-a^2)^2) - (kq * (x^2+2*x*a+a^2))/((x^2-a^2)^2) =

= kq * (- 4*x*a)/((x^2-a^2)^2)

= (kq * (x-a)^2)/((x+a)^2 * (x-a)^2) - (kq * (x+a)^2)/((x-a)^2 * (x+a)^2) =

= (kq * (x^2-2*x*a+a^2))/((x+a)^2 * (x-a)^2) - (kq * (x^2+2*x*a+a^2))/((x-a)^2 * (x+a)^2) =

= (kq * (x^2-2*x*a+a^2))/((x^2-a^2)^2) - (kq * (x^2+2*x*a+a^2))/((x^2-a^2)^2) =

= kq * (- 4*x*a)/((x^2-a^2)^2)

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment